Impact of moisture content, closing speed, and pressurizing speed on the performance of medium density fiberboard (MDF) - Gul, Waheed; Ahmad, Naveed; Mohammad, Shoaib; Salah, Bashir; Sajid Ullah, Syed; Khurram, Muhammad; Khan, Razaullah (Frontiers in Materials, 2023)
The purpose of this research is to investigate the impact of moisture content, closing speed, and pressurizing speed of hot press on the density, uniformity of density distribution, and properties of Medium Density Fiberboard (MDF) products. Moisture content affects the plasticity, heat conductivity, and hydrolysis reaction of the fiber and appropriate moisture content ensures the quality of the board. Excessive moisture content can lead to defects such as pollution and bubbles on the surface of the board. Closing time and pressurizing speed affect the nature, quality, and section structure of the MDF. The section density of the board varies with the closing time, and the product properties, especially the strength differs largely. The pressurizing speed influences the density distribution and board properties. Fast pressurizing speed results in high Modulus of Rupture (MoR) and low Internal Bonding (IB), while slow pressurizing speed leads to low MoR and high IB. Pre-plasticizing layer can improve the quality of MDF by increasing the density and hardness of the board surface. The findings provide guidance for optimizing the MDF production process and improving the quality of MDF products. Applying a fast pressurizing speed during the manufacturing process of MDF has resulted in a 15.7% increase in the MoR, which is a measure of the material's ability to withstand stress before breaking as compared to using a slow pressurizing speed. Additionally, using a fast pressurizing speed has led to a reduction of 17.4% in the IB, which is a measure of the ability of the board to resist internal separation or delamination. Therefore, a fast pressurizing speed is more effective in improving the mechanical properties of MDF.